Teknologi Pengendalian Serangan Hama Padi di Desa Pulau Rambai Kecamatan Kampa Kabupaten Kampar - Fauzana, Hafiz; Nelvia, Nelvia; Rustam, Rusli; AR, Arman Effendi; Erawati, Netti; Kurnia, Rita; Irfandri, Irfandri; Fitriana, Melani; Putri, Afra Fadhila; Yobi, Afrila (Unri Conference Series: Community Engagement, 2024)
Rice is the main food commodity grown in Pulau Rambai Village, Kampa District, Kampar Regency. Rice planting in the 2023 planting period occurred crop failure due to pest attacks. The solution offered is the extension of appropriate pest control technology applied by farmers to overcome rice pest attacks. The method of implementing the service is survey, consolidation, counseling and control practices. The measuring tool for the achievement of service activities is understanding and knowledge, a questionnaire is distributed before and after the service activity so that a percentage increase is obtained. Farmers can practice and carry out the service activities that are advised, the level of success is measured by the percentage of farmers who carry it out. The service activity was carried out at the Pulau Rambai Village Musholla on Thursday, July 25, 2024. The results of respondents from 31 farmers were rat infestation, grasshoppers, brown planthopper and snails were 93.5%. Farmers before the service answered pest control by spraying pesticides 77.4%, rats were fumigated 12.9%, mosquito nets for grasshoppers 6.45%. 100% of farmers have never used botanical pesticides. After counseling, farmers' understanding of rice pest control increased, namely controlling rat using composting and poisonous bait 28%, grasshoppers with botanical pesticides and biological agents 56%. Farmers practiced the activities that were advised in the form of control using biological agents Metarhizium sp, botanical pesticides were 27,5%.